Pandemik COVID-19: Analisis Perencanaan Pemerintah dan Masyarakat dalam Berbagai Upaya Pencegahan - Idah Wahidah; Raihan Athallah; Nur Fitria Salsabila Hartono; M. Choerul Adlie Rafqie; Muhammad Andi Septiadi (Jurnal Manajemen dan Organisasi, 2020)
The new epidemic phenomenon called Covid-19 which originated in Wuhan, China continues to increase its victims. This article aims to provide an explanation of the new outbreak and analyze planning management regarding the important role of government policies that must synergize with the community by 4 strategies from the government, namely promotive, preventive, curative and social safety net strategies which will later impact on strategies that are can the government apply in passing a pandemic disaster. The method used in writing this article is a qualitative method that explains something based on data and numbers narrated in concluding sentences, besides that, the writing of this article is library research, collecting data through available documents. and using triangulation techniques in analyzing the data that has been collected. The results obtained are the role of the government constantly reminding and asking for the participation of the community to achieve maximum government policy results, the need for the role of the community in an effort to overcome the pandemic to carry out all existing policies so that there is synergy to break the chain of spread of the COVID-19 virus and It was also found that the Head of RT / RW is one way that can assist the government in carrying out synergy with the community. This research is expected to be a source of reference for the government in planning the next policy in the process of overcoming the COVID-19 pandemic.